Valence compensated perovskite oxide system Ca1-xLaxTi1-xCrxO3. Part I: Structure and dielectric behaviour - Dwivedi R.K.; Kumar D.; Parkash O. (My University, 2025)
Attempts have been made to synthesize compositions with x = 0.01, 0.03, 0.05, 0.10, 0.20, 0.30 and 0.50 in the valence compensated system Ca1-xLaxTi1-xCrxO3 by solid state ceramic method. Solid solutions form upto x ≤ 0.50. All the compositions have been found to have orthorhombic structure. The structure of the compositions upto x ≤ 0.10 is similar to that of CaTiO3. The structure changes gradually from CaTiO3 to LaCrO3 in the composition range 0.10 < x < 0.50. Dielectric constant, at room temperature, has been found to increase with increasing substituent concentration upto x = 0.30 and thereafter it decreases with increasing x upto 0.50. Orientational and space charge polarizations contribute to the dielectric behaviour of these materials. © 2001 Kluwer Academic Publishers.